2022
DOI: 10.1007/s00167-022-07251-5
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch between trochlear coronal alignment of arthritic knees and currently available prosthesis: a morphological analysis of 4116 knees and 45 implant designs

Abstract: Purpose In up to a fifth of total knee replacements (TKR), surgeons are not capable of achieving good clinical and functional results. Despite comprehensive diagnostic workup, an underlying cause is not always identified in these patients. The purpose of this study is to compare native and prosthetic trochlear anatomies, to evaluate a potential source of morphologic mismatch and theoretically, of poor clinical outcomes. Methods Native trochlear angles of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The 2D radiographic findings of the present study, which showed a femoral component with a PTA of 6° valgus did not include the Q-angle in MA TKA simulations, is consistent with 3-D analysis studies that showed that MA TKA does not restore native trochlear morphology [14,22,24]. For example, a study of 45 femoral component designs aligned mechanically in 4116 3-D CT femoral models showed that 41% of the PTA fell out of the range of the native trochlear angle, representing a potential source for biomechanical imbalance, which manufacturers may need to take into account for future implant designs [24]. Another 3-D analysis showed the optimal target for aligning the femoral component is not the FMA because the QV passes lateral to the femoral head center [16].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The 2D radiographic findings of the present study, which showed a femoral component with a PTA of 6° valgus did not include the Q-angle in MA TKA simulations, is consistent with 3-D analysis studies that showed that MA TKA does not restore native trochlear morphology [14,22,24]. For example, a study of 45 femoral component designs aligned mechanically in 4116 3-D CT femoral models showed that 41% of the PTA fell out of the range of the native trochlear angle, representing a potential source for biomechanical imbalance, which manufacturers may need to take into account for future implant designs [24]. Another 3-D analysis showed the optimal target for aligning the femoral component is not the FMA because the QV passes lateral to the femoral head center [16].…”
Section: Discussionsupporting
confidence: 89%
“…However, as presented in Fig. 1, most of the femoral components from the major implant manufacturers have a PTA of 6° valgus, similar to the one evaluated in the present study [24]. Finally, the present study did not evaluate the clinical consequences of medial and lateral deviation for MA TKA, so it remains unknown whether the adverse clinical consequences of medial deviation of the PTA reported for unKA also apply to MA TKA without further study.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations